Dž. Čoseris ir prerenesanso problema - Varnaitė, Irena (Literatūra, 1974)
he fourteenth century brought to England the most favourable conditions for different pre-Renaissance movements. Chaucer is the most prominent figure in English pre-Renaissance literature. What distinguishes Chaucer from his French and English contemporaries is the fact that he, beginning with his earliest works, draws his characters by means of realistic detail, motivates their behaviour, and reveals their inner world. Quite a number of full-blooded characters show how successfully Chaucer was furthering himself from the mediaeval tradition of court literature and its types and approaching the Renaissance conception of man. Not able to fully get rid of mediaeval literary traditions, very often did the poet subject them to mockery, as in "Troilus and Criseyde," to satire, as in the "Parliament of Fowls," or to open parody of the genre of court romances, as in "Sir Thopas." This is utterly new in English literature.Chaucer's literary career witnesses his evolution towards realism: from separate characters drawn in a realistic manner and the inserted realistic narratives (which, to some extent, change the character of the traditional mediaeval genre of a dream-vision) to a realistic novella, a typical genre of the New Times. The personality of the poet also appears in a new light in his works. The poem "Troilus and Criseyde" and the "Canterbury Tales" bring Chaucer nearest to the Renaissance; it is in them that the literary tendencies of the pre-Renaissance are most tangible.